Evaluation of the coefficient of friction of rail in the field and laboratory using several devices. (2nd April 2020) - Harmon, M.; Santa, J. F.; Jaramillo, J. A.; Toro, A.; Beagles, A.; Lewis, R.
ABSTRACT: Accurate friction measurement is vital to apply appropriate friction management techniques to the wheel/rail interface. This work analyses different friction measurement techniques under a variety of conditions in the laboratory and the field. Tests have been carried out using a pendulum tester, hand-push tribometer, twin-disc machine and full-scale rig in the UK and Colombia for a variety of interfacial conditions and rail hardness. The pendulum has been found to be more sensitive to different conditions than the hand-push tribometer. This is due to the area that the pendulum sweeps being smaller, and so it can be more carefully controlled and therefore measure the surface condition being tested. This is in contrast to the push tribometer which needs a long section of rail to take a measurement. Twin-disc and full-scale rig creep curves show good agreement between each other.